Molecular mechanisms of building blocks of life towards medicinal applications - Nureki, Osamu (Keio journal of medicine, 2022)
Membrane and membrane-spanning proteins, and non-coding RNA are biomolecules to play central roles in beginning of life and distinguishing higher-order eukaryotes. We have determined the structures of membrane protein-lipids complexes and non-coding RNA-protein complexes by X-ray crystallography and Cryo-EM single particle analysis, and combined with complementary functional analyses, elucidate their molecular mechanisms at atomic resolutions, to promote creating drugs and medical technologies with two venture companies.